Frozen in time : permafrost and engineering problems - Muller, Siemon W. 1900-1970 (Technical Council on Cold Regions Engineering monograph., 2008)
"This book reads like a "how-to" manual for engineering personnel working in pioneering or primitive circumstances. The book reviews the large Russian-language body of literature devoted to permafrost, but also covers work published in English during the intervening years. It addresses topics such as basic scientific knowledge about perennially frozen ground and the engineering problems associated with it, the geography of permafrost, related elements of landscape science and ecology, periglacial geomorphology, and the physics of frozen ground. This book serves as a valuable historical document, and will also be useful for those seeking basic knowledge about permafrost and approximate methods for coping with associated engineering problems."--Jacket.